Breastfeeding and sexual difference: Queering Irigaray. (April 2018) - Lee, Robyn
It is commonly assumed that only women, and in particular women who have recently given birth, are able to breastfeed. However, through induced lactation, adoptive mothers, fathers and trans people have begun breastfeeding with greater frequency. Although breastfeeding is often regarded as a paradigmatic example of sexual difference, it actually exposes the instability of binary categories of sex. Luce Irigaray insists that sexual difference demands a new poetics, a language that is dynamic and fluid, capable of expressing difference while always keeping open the possibility of transformation and change. This article extends Irigaray's work in order to theorise breastfeeding from a perspective that is both feminist and queer.